A brief analysis of the outsourcing industry in Romania - Andreea Burciu; Mihaela Mihai (Romanian Economic Journal, 2015)
Outsourcing is rather a new way of doing business and optimising a company's processes. The paper offers an overview of the definitions of the term, which are the benefits and the risks of the choice of outsourcing and how should this decision be made. Using various sources, we tried to create a proper image of this industry and explain what it will be still growing in the future. The study aims to address the global landscape and then focus on Romania's position on the market by using data provided by the National Bank of Romania and the International Monetary Fund, as well as consultancy companies.